Experimental Investigation on Cracking Characteristics of Dry and Saturated Shales in Nitrogen Fracturing after Liquid Nitrogen (LN2) Injection. (13th April 2023) - Zhang, Yan; Wu, Yu; Vadimovna, Savenok Olga; Yin, Jiadi; Geng, Haozhe; Li, Decheng
Abstract : Cryogenic LN2 fracturing is one of the environmentally friendly waterless fracturing technologies that promote the fracture complexity of shale gas reservoir. The water-ice phase transition under freezing condition causes frost heave in saturated shale. The effect of moisture in shale should be taken into account during cryogenic damage process. Therefore, the differences of cracking characteristics between dry and saturated shales were studied in this paper. A laboratory triaxial and high temperature fracturing system was developed for nitrogen fracturing dry and saturated shale after LN2 injection. The influence of moisture on breakdown pressure was studied under different confining pressures (3 MPa, 6 MPa, 9 MPa, and 12 MPa) and bedding directions (parallel bedding and vertical bedding). The experimental results demonstrated that when the confining pressure increased from 3 MPa to 12 MPa, the breakdown pressure of dry parallel bedding after LN2 preconditioning decreased 7.12 MPa, 6.06 MPa, 4.58 MPa, and 3.11 MPa, respectively. Therefore, LN2 preconditioning could damage shale resulting in a lower breakdown pressure, but the effect of cryogenic damage decreased with the confining pressure increasing. The moisture in shale had little impact on nitrogen fracturing without LN2 injection because the breakdown pressure difference between dry and saturated shales was small. However, the breakdown pressure of saturated shale after LN2 preconditioning was always lower than that of dry shale. The breakdown pressure of saturated parallel bedding shale after LN2 injection decreased 8.62 MPa, 7.67 MPa, 6.08 MPa, and 4.63 MPa, respectively, with the confining pressure increasing from 3 MPa to 12 MPa. The breakdown pressure difference between dry and saturated shales was impacted by the migration of unfrozen water and frost heave. In addition, the extent of cryogenic damage varied substantially between different bedding directions. When the confining pressure was 3 MPa, the breakdown pressure of saturated parallel bedding shale reduced by 69.18% after LN2 preconditioning, but that of saturated vertical bedding shale only decreased by 22.49%. The tensile strength of shale had a greater influence on the breakdown pressure. According to the Brazilian disc test results, the tensile strength of matrix was much higher than that of bedding planes. As a result, it is useful to wet the shale in order to reduce the breakdown pressure. The fracturing direction of horizontal drilling should be consistent with the bedding direction for better cryogenic fracturing effect.